Differences in Primary School Students’ Intercultural Competences Based on School Location - Tomić, Marija Ž.; Mikanović, Brane R. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Intercultural skills have become essential for functioning in contemporary society, where daily interaction with members of diverse cultures and adaptation to different cultural environments are increasingly necessary. Integration into such environments requires the development of new forms of behavior and approaches. Core values such as openness to diversity and strong communication skills have become key factors for functioning in these social conditions, and should be encouraged from an early age. An upbringing that enables children to participate in multicultural communities significantly contributes not only to their personal development but also to the improvement of society as a whole. The ability to develop intercultural competences helps individuals navigate relationships within various ethnic, religious, and national groups, which is crucial for the overall progress of society. This paper analyzes how primary school students assess their own intercultural competences, taking into account the location of the school they attend. Data were collected using a self-assessment scale for intercultural competences. The results of the study indicate statistically significant differences in self-assessment, favoring students attending urban schools. These findings open avenues for further research to better understand the underlying causes of these differences.
Keywords: primary school students’ intercultural competences; urban schools; suburban schools